CONVERSION TO OPEN SURGERY AFTER ENDOVASCULAR ABDOMINAL AORTIC ANEURYSMS REPAIR - Utikal, Petr; Koecher, Martin; Koutna, Jirina; Bachleda, Petr; Drac, Petr; Cerna, Marie (Biomedical papers, 2006)
The authors describe experience with conversions to open surgery after endovascular abdominal aneurysm repair and evaluate the frequency, causes and results of a total of 7 cases in their series of 165 patients treated over a 10-year period.
Keywords: Aorta/Aneurysms/Repair/Endovascular/Open Surgery/Complications/Conversion